BACTERIOLOGICAL INVESTIGATION OF PRAWN CANNERIES I. INCIDENCE OF AEROBIC SPOREFORMERS - NAMBIAR, V NARAYANAN; IYER, K MAHADJEVA (Fishery Technology, 2025)
A detailed bacteriological survey of the prawn